Effects of Microparameters on Macroparameters of Flat-Jointed Bonded-Particle Materials and Suggestions on Trial-and-Error Method - Chen, Peng-yu (Geotechnical and geological engineering, 2017)
The aims of this paper are to analyze the effects of microparameters on macroparameters of flat-jointed bonded-particle materials of particle flow code in two dimensions (PFC2D) and improve the efficiency of trial-and-error method in calibration of microparameters. The trial-and-error method is always used to calibrate the microparameters for a PFC2D model, but it is time-consuming and empirical. To improve the efficiency of the trial-and-error method, the effects of microparameters on macroparameters need to be analyzed. By using the trial-and-error method, a desirable set of microparameters for a uniaxial compression PFC2D model (with a flat-joint contact model as the contact model) of limestone were calibrated to match the macroscopic properties obtained from laboratory tests. Based on the calibration set of microparameters, effects of microparameters on macroparameters of the PFC2D model were studied by the orthogonal design method. On this basis, a flowchart of calibrating microparameters via trial-and-error method was proposed. This flowchart was used to calibrate the microparameters of granite. The macroparameters and failure characteristics determined from numerical simulation were very similar to those of laboratory tests, confirming the effectiveness of the proposed flowchart.